2014
DOI: 10.1523/jneurosci.2111-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Restriction Impairs Blood–Brain Barrier Function

Abstract: The blood-brain barrier (BBB) is a large regulatory and exchange interface between the brain and peripheral circulation. We propose that changes of the BBB contribute to many pathophysiological processes in the brain of subjects with chronic sleep restriction (CSR). To achieve CSR that mimics a common pattern of human sleep loss, we quantified a new procedure of sleep disruption in mice by a week of consecutive sleep recording. We then tested the hypothesis that CSR compromises microvascular function. CSR not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 34 publications
5
142
1
2
Order By: Relevance
“…Active transport of substances across the BBB is controlled by the CNS, and differs in consequences from passive diffusion or unregulated leakage that is associated with BBB dysfunction. BBB active transport mechanisms are influenced by sleep and circadian processes (Pan and Kastin, 2016) and by sleep disruption (He et al, 2014). Within the context of sleep and CNS-immune interactions, the active transport of cytokines (Banks et al, 1991;Gutierrez et al, 1993;Plotkin et al, 1996), notably IL1, IL6, and TNF, is likely an important contributor to changes in sleep that occur during prolonged disease or infection.…”
Section: Blood To Brain Transport Mechanismsmentioning
confidence: 99%
“…Active transport of substances across the BBB is controlled by the CNS, and differs in consequences from passive diffusion or unregulated leakage that is associated with BBB dysfunction. BBB active transport mechanisms are influenced by sleep and circadian processes (Pan and Kastin, 2016) and by sleep disruption (He et al, 2014). Within the context of sleep and CNS-immune interactions, the active transport of cytokines (Banks et al, 1991;Gutierrez et al, 1993;Plotkin et al, 1996), notably IL1, IL6, and TNF, is likely an important contributor to changes in sleep that occur during prolonged disease or infection.…”
Section: Blood To Brain Transport Mechanismsmentioning
confidence: 99%
“…Chronic sleep deprivation might also act via increased blood-brain barrier (BBB) permeability [26]. BBB disruption occurs early in the sequence of events leading to acute exacerbation in individuals with MS [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this fi eld make a distinction between total sleep deprivation (absence of sleep) 2 , chronic sleep restriction 3 , and the situation of sleep disruption/sleep fragmentation 4 . Total sleep deprivation denotes a lack of sleep for a specifi c period of time (one night at least) extending to a longer period of wake (in some studies even more than 72 h) 5,6 .…”
Section: Methodology Of Sleep Deprivation Studiesmentioning
confidence: 99%
“…Modern society often makes it imperative to increase productivity, even at the cost of sleep deprivation. However, research has shown that it is not wise because a longer period of sleep deprivation or chronic shortening of its duration will necessarily lead to a decline of cognitive functions in individuals, thus also leading to a decline in the quality of their productivity [1][2][3][4] . Sleeping is a natural state of the human body, which involves cyclic alternation of two main stages, non-rapid-eye movement (NREM) sleep and rapid-eye movement (REM) sleep.…”
Section: Introductionmentioning
confidence: 99%